1991
DOI: 10.1192/bjp.159.2.250
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nutritional Management with Stress Management in the Treatment of Bulimia Nervosa

Abstract: In a comparison of nutritional management (NM) and stress management (SM) for treatment of bulimia nervosa, 55 female patients were randomly assigned to either treatment. Therapy consisted of 15 sessions in a group over three months, by the end of which, patients under both treatment conditions showed a significant reduction in the frequency of binge eating and vomiting and a significant improvement in various psychopathological features such as body dissatisfaction and depression. All improvements were mainta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 30 publications
1
43
0
4
Order By: Relevance
“…A trend emerged among studies' reports of treatment efficacy: treatment outcome studies tended to favor treatment interventions as predicting positive outcome (23,24,28,33,39,61,62), while naturalistic studies found previous treatment interventions to be unassociated with outcome (4,8,9,17,59). Two exceptions to this pattern exist.…”
Section: Treatmentmentioning
confidence: 87%
“…A trend emerged among studies' reports of treatment efficacy: treatment outcome studies tended to favor treatment interventions as predicting positive outcome (23,24,28,33,39,61,62), while naturalistic studies found previous treatment interventions to be unassociated with outcome (4,8,9,17,59). Two exceptions to this pattern exist.…”
Section: Treatmentmentioning
confidence: 87%
“…Com os unitermos utilizados, apenas seis artigos publicados no Brasil foram encontrados 25,26,[36][37][38] , sendo apenas dois com foco no tratamento nutricional da BN 25,26 . Na literatura internacional, a busca com esses unitermos resulta em estudos sobre o papel de neurotransmissores e peptídeos [39][40][41] , tratamentos combinados [42][43][44][45][46] , e alguns com foco específico no tratamento nutricional [47][48][49] .…”
Section: Perspectivas De Continuidade Das Pesquisas Na áReaunclassified
“…Esses trabalhos apontam que o tratamento nutricional deve ser visto como uma primeira intervenção necessária 42 , para todos os pacientes; que a intervenção nutricional é efetiva para BN -com melhoras mantidas em três meses de segui-mento- 44 e que a TCC combinada à terapia nutricional permanece como tratamento de escolha para BN 45 .…”
Section: Perspectivas De Continuidade Das Pesquisas Na áReaunclassified
See 1 more Smart Citation
“…For example, Laessle et al (1991) compared what they called a nutritional management (NM) treatment with stress management. The former closely approximated the behavioral components (Stage 1) of manual-based CBT (Fairburn et al, 1993).…”
Section: A Rose By Any Other Namementioning
confidence: 99%